Orbital Simulations on Deflecting Near-Earth Objects by Directed Energy. (14th March 2016) - Zhang, Qicheng; Walsh, Kevin J.; Melis, Carl; Hughes, Gary B.; Lubin, Philip M.
Abstract: Laser ablation of a near-Earth object (NEO) on a collision course with Earth produces a cloud of ejecta that exerts a thrust on the NEO, deflecting it from its original trajectory. Ablation may be performed from afar by illuminating an Earth-targeting asteroid or comet with a stand-off "DE-STAR" system consisting of a large phased-array laser in Earth orbit. Alternatively, a much smaller stand-on "DE-STARLITE" system may travel alongside the target, slowly deflecting it from nearby over a long period. This paper presents orbital simulations comparing the effectiveness of both systems across a range of laser and NEO parameters. Simulated parameters include magnitude, duration and, for the stand-on system, direction of the thrust, as well as the type, size, and orbital characteristics of the target NEO. These simulations indicate that deflection distance is approximately proportional to the magnitude of thrust and to the square of the duration of ablation, and is inversely proportional to the mass. Furthermore, deflection distance shows strong dependence on thrust direction with the optimal direction of thrust varying with the duration of laser activity. As one example, consider a typical 325 m asteroid: beginning 15 years in advance, just 2 N of thrust from a ∼20 kW stand-on DE-STARLITE system is sufficient to deflect the asteroid by . Numerous scenarios are discussed as is a practical implementation of such a system consistent with current launch vehicle capabilities.